Identifikasi Senyawa Aktif Ekstrak Buah Mengkudu (Morinda citrifolia L.) dan Potensinya sebagai Inhibitor Karies Gigi - Sogandi, Sogandi; Nilasari, Putu (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Dental caries is a disease that many people experience, which is formed by the buildup of plaque on the teeth and the presence of bacteria. The bacteria known to be involved in the formation of dental caries is Streptococcus mutans. Dental caries used to be treated using antibiotics. However, it is known that many antibiotics are no longer effective against this bacteria hence it is necessary to look for another alternative. One alternative choice as an antibacterial is Noni fruit. This study aims to identify the bioactive compounds of noni fruit (Morinda citrifolia L) and to know the mechanism of action in inhibiting the growth of Streptococcus mutans. Noni fruit was macerated using 96% ethanol, then fractionated using n-hexane and ethyl acetate. Antibacterial activity test was done using agar difusion method, and identification of bioactive compounds was conducted using GCMS. The results showed that ethyl acetate fraction has the highest inhibitory activity on the growth of Streptococcus mutans with inhibition zone of ±17 mm and MIC (minimum inhibitor concentration) value of 10%. The inhibition mechanism is asumed to be done by making holes in cell membranes, which can be seen from the high concentration of proteins and nucleic acids coming out of cells after treatment that in turn means that cell leakage has occurred. The results of this study indicate that noni fruit (Morinda citrifolia L) contain bioactive quinolone compounds that can be a new source for treating dental caries